Feedforward nonlinear PID control of a novel micromanipulator using Preisach hysteresis compensator. (August 2015) - Tang, Hui; Li, Yangmin
Abstract: Recently, flexure-based micromanipulators with a large workspace, high motion precision, and high positioning bandwidth are really attractive for performing practical micro/nano manipulation tasks. Thus, a piezo-actuated flexible two-degrees-of-freedom (2-DOF) micromanipulator integrated with a pair of modified differential lever displacement amplifiers (MDLDA) is developed. To enhance the practical positioning performance of the micromanipulator, a novel feedforward nonlinear Proportion-Integration-Differentiation (FNPID) control strategy combining a nonlinear PID controller with an inverted hysteresis compensator is first proposed and implemented in detail. With the consideration of hysteresis effect inherent in piezoelectric ceramics (PZT) actuators, the hysteresis nonlinearity modeling is conducted by using the Preisach theory. Finally, a series of precision motion trajectory tracking experiments are successfully conducted by using the proposed closed-loop control strategy. The experimental results indicate that the mechanism has achieved a satisfactory performance for performing robotic biomanipulations. Abstract : Highlights: A novel FNPID controller for the improvement of the practical working frequency of the flexure-based nanopositioning system is proposed. A new concept named "area efficiency" is proposed to make a quantitative evaluation for the designed nanomanipulator. Preisach method is adopted to model and compensate the complicated hysteresis nonlinearity. A series of trajectory tracking experiments are conducted to make comparisons between the proposed FNPID and PID controller.